Implementation of the Article 32 of Government Regulation Number 24 of 2016 Concerning Land Deed Official Honorarium: Study at the land deed official office located in the working area in situbondo - Malik Hariyanto; Prija Djatmika; Diah Aju Wisnuwardhani (Faculty of Law, University of Jember, Indonesia, 2024)
The regulation regarding honorarium does not mention a definite amount or proportion, but only determines the upper limit preceded by the word â€œmay not exceedâ€ 1% (one percent) of the transaction price stated in the deed as stipulated in Article 32 paragraph (1) of Government Regulation No. 24 of 2016 amending Government Regulation No. 37 of 1998 on the Regulation of the Position of Land Deed Makers. This certainly raises problems related to the absence of certainty regarding the amount of honorarium so that it allows for differences in rates between PPATs with one another. This research was conducted with the aim of revealing whether the implementation of the determination of PPAT honorarium carried out by a PPAT at the PPAT Office located in the Working Area in Situbondo is in accordance with the provisions of Law Number 24 of 2016 Article 32 concerning PPAT Honorarium and the factors that hinder the implementation of Article 32 of Law Number 24 of 2016 concerning PPAT honorarium. This research is designed using juridical-empirical research methods. The results of this study indicate that the implementation of honorarium in Situbondo district is not fully in accordance with the provisions of Article 32 of Law Number 24 of 2016 concerning PPAT honorarium. Factors causing obstacles to the implementation of the provisions of Law Number 24 of 2016 Article 32 concerning PPAT Honorarium in Situbondo because the rules do not also provide a salary for the PPAT. KEYWORDS: Honorarium, PPAT, Deed